The graduate survival guide : 5 mistakes you can't afford to make in college - ONeal, Anthony; Cruze, Rachel (Ramsey Press, the Lampo Group, LLC, 2017)
A manual to help high school graduates avoid the five mistakes a large majority of college students make. These mistakes may cause you years and years of pain and hardship if you too follow the path of so many others.